ENHANCING CHRONIC DISEASE SCREENING EFFICIENCY VIA MODERN INFORMATION TECHNOLOGIES - Khodjieva Gulirano Sayfullaevna (Modern American Journals, 2025)
This article describes the results of a study on the adaptation, implementation and evaluation of the effectiveness of the MyTherapy mobile application in the practice of treating chronic non-infectious diseases in order to monitor treatment and patient compliance. Based on the more pronounced positive dynamics of the therapy itself, the improvement in the quality-of-life indicator and the indicator of adherence to treatment, it is shown that the use of this mobile application can be a highly effective method of monitoring the therapy of chronic non-infectious diseases when used correctly.
Keywords: anemia; compliance; therapy control; mobile applications.